CALAMOS Closed-End Funds (CHI, CHY, CSQ) Announce Monthly Dividends (PR Newswire, 2005)
The dividend offers shareholders the opportunity to accumulate more shares in the Fund via the automatic dividend reinvestment plan. For example, if the Fund's shares are trading at a premium, dividends will be automatically reinvested through the plan at NAV or 95% of the market price, whichever is greater; if shares are trading at a discount, dividends will be reinvested at the market price. Thus, the plan offers current shareholders an efficient method of accumulating additional shares with a potential for cost savings. Please see the dividend reinvestment plan for more information.